1992
DOI: 10.1007/bf00541566
|View full text |Cite
|
Sign up to set email alerts
|

Chemically deposited n-CdSe thin film photo-electrochemical cells: effects of Zn2+-modification

Abstract: The photoelectrochemical solar cell properties of chemically deposited n-CdSe films were studied before and after Zn 2+ surface modification. It was shown that the surface properties underwent conceivable changes after Zn 2+ treatment. The current-voltage characteristics in the dark showed a significant decrease in reverse saturation current density, Jo, from 5.4 x 10 -7 to 1.2 x 10 _9 Acm -2 and in ideality factor, n, from 2.46 to 1.27. Under AM1 illumination, other parameters have been found to be considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Bis(n-hexy (methyl)dithio/selenocarbamato)cadmium/zinc proved to be the best of the unsymmetrical derivatives for the growth of chalogenides [18][19][20][21][22] caused by undesirable ligand degradation reactions. Other methods used to deposit CdSe thin films include vacuum evaporation and co-evoparation [30] molecular beam deposition [31], laser ablation [32], electrochemical deposition [33][34][35], spray pyrolysis [36][37][38], and chemical bath deposition [3,[38][39][40][41][42][43][44]. A convenient and controllable hydrothermal synthetic method based on a reaction in an aqueous system to produce CdSe nanostructures of different sizes and shapes was reported [44].…”
Section: Introductionmentioning
confidence: 99%
“…Bis(n-hexy (methyl)dithio/selenocarbamato)cadmium/zinc proved to be the best of the unsymmetrical derivatives for the growth of chalogenides [18][19][20][21][22] caused by undesirable ligand degradation reactions. Other methods used to deposit CdSe thin films include vacuum evaporation and co-evoparation [30] molecular beam deposition [31], laser ablation [32], electrochemical deposition [33][34][35], spray pyrolysis [36][37][38], and chemical bath deposition [3,[38][39][40][41][42][43][44]. A convenient and controllable hydrothermal synthetic method based on a reaction in an aqueous system to produce CdSe nanostructures of different sizes and shapes was reported [44].…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification by ZnCl 2 treatments was reported to increase the quantum efficiencies. The growth of a thin SeO 2 layer was thought to be responsible for the muchimproved film stability, while the increase in band bending and shift in Fermi level were reported to be due to additional surface charges provided by the Zn 2+ ions [6]. Earlier reports on ZnCl 2 surface modification [1,[7][8][9], that indicated that this treatment causes a decrease in dark current, are consistent § Author to whom correspondence may be addressed.…”
Section: Introductionmentioning
confidence: 74%
“…While the results of ZnCl 2 surface modification reported an increase in both short circuit current and stability [6], the improvement in photocurrent has usually been correlated to a decrease in long term stability. That was the case in CdSe films coated with a thin film (350 Å) of ZnO [10] where the improvement in stability was obtained at the expense of cell performance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Efficient electron injection from the photoexcited QD into the TiO 2 conduction band requires close QD-TiO 2 contact. Deposition of CdSe-QD layers on a conducting transparent substrate (usually fluorine doped tin oxide-FTO) covered with nano-crystalline(NC)-TiO 2 by using simple dipping has been reported to be applicable (direct absorption-DA) [19][20][21][22][23]. Anchoring QDs on TiO 2 by linker molecules containing both carboxylate and thiol functional groups is another approach to achieve close and stable contact (linker technique) [12,21,24].…”
Section: Introductionmentioning
confidence: 99%